Ansichten von Geographielehrkräften zum kompetenzorientierten Unterricht und ihr Zusammenhang mit Überzeugungen: Ergebnisse einer empirischen Befragung - Horn, Michael; Schweizer, Karin (Journal of Geography Education, 2015)
Research about competency-based education is mainly focused on the development of students’ competencies or on theoretical approaches at and empirical tests of competency-based education. In contrast, the examination of teachers' views on competency-based education in Geography shows a lack. After a small-sized preliminary study (n = 44) a representative sample of teachers for secondary schools from Rhineland-Palatinate and Baden-Württemberg (n = 95) was therefore inquired by means of a survey. Thereby, the questions whether the publicity of the National Educational Standards differs between the two provinces, different kinds of secondary schools or with teaching experience could be answered. Surprisingly more than the half of the teachers was not familiar with the Standards. Another objective was to look at the relationship between their views on competency-based education and epistemological beliefs which are regarded as affecting classroom teaching and the fact whether both kinds of assumptions and beliefs are dependent on teaching experience. The results show that experienced teachers agreed less with given statements to competency-based education than teachers with less teaching experience. Nevertheless we have not found a correlation between teaching experience and epistemological beliefs even though splitting the sample by teaching experience reveals a stronger correlation between both kinds of beliefs.
Keywords: competency based education, epistemological beliefs, survey study, National Educational Standards in Geography